2019
DOI: 10.2147/ott.s186923
|View full text |Cite|
|
Sign up to set email alerts
|

<p>LncRNA SNHG16 drives proliferation and invasion of papillary thyroid cancer through modulation of miR-497</p>

Abstract: BackgroundLong noncoding small nucleolar RNA host gene 16 (SNHG16) has been shown to play an oncogenic role in multiple cancers. However, the biological roles and mechanism of SNHG16 action in the regulation of papillary thyroid cancer (PTC) remains unknown. The aims of this study were to investigate the roles and the possible mechanism of SNHG16 in PTC progression.Materials and methodsThe expression of SNHG16 PTC tissues and cell lines was detected by reverse-transcription quantitative PCR (qRT-PCR). The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…However, the biological role of SNHG16 and its underlying mechanism in DLBCL are still unknown. SNHG16 acts as a molecular sponge for miR‐497‐5p to promote the proliferation and invasion of papillary thyroid cancer cells . miR‐497‐5p is underexpressed in human primary NPM‐ALK+ primary lymphoma and inhibits cell cycle progression in cancer cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the biological role of SNHG16 and its underlying mechanism in DLBCL are still unknown. SNHG16 acts as a molecular sponge for miR‐497‐5p to promote the proliferation and invasion of papillary thyroid cancer cells . miR‐497‐5p is underexpressed in human primary NPM‐ALK+ primary lymphoma and inhibits cell cycle progression in cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…SNHG16 acts as a molecular sponge for miR-497-5p to promote the proliferation and invasion of papillary thyroid cancer cells. 25 miR-497-5p is underexpressed in human primary NPM-ALK+ primary lymphoma and inhibits cell cycle progression in cancer cells. 26 Additionally, miR-497-5p functions as a tumour suppressor via targeting the Raf-1-mediated MAPK/ERK pathway in multiple myeloma cells.…”
Section: Introductionmentioning
confidence: 99%
“…41 Wen et al found that knockdown of SNHG16 inhibits migration and invasion of TPC-1 cells via regulating miR-497. 42 Interestingly, Vahid found a correlation between SNHG16 expression and the vitamin D receptor (VDR), which supports the hypothesis of an interactive network between SNHG16, VDR, and miR-98 in the context of cancer. 59 SNHG16 is expected to become a novel molecular marker for diagnosis, prognosis, and treatment of BC.…”
Section: Activating Migration and Invasionmentioning
confidence: 60%
“…41 SNHG16 is upregulated in both papillary thyroid tissues and cell lines, which indicates advanced TNM stage and lymph node metastasis. 42 In addition to sequencing in tumor tissues, lncRNA levels can also be measured in exosomes. Exosomes, which are microvesicles (70-120 nm) derived from endosomes secreted by many cell types, can participate in intercellular communication by transferring intracellular substances (such as proteins, lipids, and nucleic acids, including lncRNA).…”
Section: Overexpression Of Snhg16 and Clinical Significance In Cancermentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) is the main histological type of thyroid cancer, accounting for >80% of all thyroid malignancies (1). Although most patients with PTC have low recurrence rate and exhibit optimal prognosis as determined by long term follow-up, approximately 15% of patients demonstrate aggressive behavior and poor outcome (2,3). To date, the pathogenesis of PTC has not been fully identified.…”
Section: Introductionmentioning
confidence: 99%